Penguatan Kompetensi Kader Kesehatan dalam Deteksi Dini Stunting dan Tumbuh Kembang Balita di Desa Dopang Gunung Sari Lombok Barat - Khair, Ziadul; Hotimah, Husnul (UNITY: Journal of Community Service, 2024)
Stunting is a critical public health issue with long-term impacts on physical growth and cognitive development in children under five. Empowering health cadres, who serve as the frontline of community health services, is vital for early detection of stunting and providing appropriate growth and development stimulation. This study aimed to enhance the competencies of health cadres in Dopang Village, Gunung Sari District, West Lombok, through interactive module-based training and hands-on field practice. A quasi-experimental approach was applied, involving 30 health cadres as participants. The results indicated a significant improvement in the knowledge, skills, and confidence of cadres in conducting anthropometric measurements, interpreting growth and development data, and educating parents of young children. This intervention also strengthened community engagement in supporting child health programs. In conclusion, strengthening the competencies of health cadres through integrated training can be an effective strategy to prevent stunting and optimize child growth and development at the community level.